INTERNAL AUDIT ACTIVITY BASED MANAGEMENT UNTUK MENILAI EFESIENSI DAN EFEKTIFITAS PADA DEPARTEMEN PRODUKSI CV. HERBA BAGOES MALANG KOTA - Ratnawati, Tri; Kusniawati, Amelia (Universitas 17 Agustus 1945 Surabaya, 2016)
In the market competition, many UKM (small and medium sized business) as the manufacturers of Herbal medicine, better known as IKOT (Traditional Medicine Small Industries) have not been able to expand its business due to the lack of capital to meet consumer demand and yet to adopt reporting systems accounting effectively and efficiently. It was thus making the IKOT have not been able to minimize the cost of production. It is therefore needed an necessary training in preparing the accounting reports that can be used to support cost savings. So, we need an application of proper accounting system in the form of the system of Activity Based Management. Activity Based Management is an integrated approach that uses cost of activities efficienciently and effectively, and thus can provide added value for customers and increasing profits as well. The purpose of this study was to Assess the Role of Internal Audit in the Implementation of Activity Based Management and evaluate how efective and effecient the implementation of Activity Based Management . This research is conducting by using qualitative techniques, mathematical techniques and analytical techniques that consists some stages of identifying the activity, analyzing segregation, analyzing the cost drivers, analyzing the activity charges, as well as the analyzing of the performance measurement activities. Then, the results were classified by the conditions, criterias, causes, consequences to provide some recommendations on the raised issues. The survey results revealed that CV. Herba Bagoes has not been implementing Activity Based Management but has been using a system of Activity Based Costing. By implementing Activity Based Management, It can minimize the cost of up to 1.30%. Activities that are non value-added to the CV. Herba Bagoes are sortaging, washing (purificating) and storaging. Storaging can be removed, while the purification activity can be replaced with immersion and storage activities can be minimalized. To overcome the problems occurred, CV. Herba Bagoes need to implement Activity Based Management.Keywords: Internal Audit, Efficiency and Effectiveness, Activity Based Management